2014
DOI: 10.2478/v10222-012-0087-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Suitability of Incorporating Tiger Nut Flour as Novel Ingredients in Gluten Free Biscuit

Abstract: late gluten-free bakery products. The gluten-free bakery products available on the market present poor organoleptic quality, not comparable to wheat ones. Research and development is needed to improve the structure, mouth feel, texture, acceptability and shelf-life of these products. Results from a number of recent studies have highlighted the need for an improvement in the quality of cereal based gluten-free products. Reduced volume, tough and/or dense texture, and reduced flavor development are among the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 18 publications
(18 reference statements)
3
27
0
Order By: Relevance
“…Carbohydrate contents of crackers decreased with the addition of tigernut flour from 56.34% for the control samples, and proportionally to 48.43% for TF4 samples. Similar results were reported by Ahmed and Hussein (2014). Means in the same column followed by the same letter have no significantly differences.…”
Section: Results and Discussion Physical Characteristics Of The Prepasupporting
confidence: 79%
See 2 more Smart Citations
“…Carbohydrate contents of crackers decreased with the addition of tigernut flour from 56.34% for the control samples, and proportionally to 48.43% for TF4 samples. Similar results were reported by Ahmed and Hussein (2014). Means in the same column followed by the same letter have no significantly differences.…”
Section: Results and Discussion Physical Characteristics Of The Prepasupporting
confidence: 79%
“…Changes in diameter and thickness were the reason that gave a reduction in spread ratio from 8.83 for control samples and gradually to 8.5, 8.25, 8.05 and 7.6 for TF1, TF2, TF3 and TF4 samples, respectively. On contrast, Ahmed and Hussein (2014) reported that the spread of the biscuits increased significantly when tigernut flour was increased in the formulation.…”
Section: Results and Discussion Physical Characteristics Of The Prepamentioning
confidence: 88%
See 1 more Smart Citation
“…The color intensity of the composite flour blends were measured using a Konica Minolta Colour Measuring System (Chroma meter CR‐410, Minolta LTD Japan) as described by Ahmed and Hussein ().…”
Section: Methodsmentioning
confidence: 99%
“…Average value for weight was reported in grams. Spread ratio was calculated by dividing diameter by thickness. Texture profile analysis of biscuit samples: Hardness and fracturability analysis of the biscuit samples were determined using the TA‐XT Plus texture analyzer (Stable Micro Systems Serial No. 5014 England) according to the method described by Ahmed and Hussein (). The analyzer was set to perform single‐cycle measurements which were used for the determination of the first bite force of the product.…”
Section: Methodsmentioning
confidence: 99%